Performance of different protocols on in vitro tuberization in potato (Solanum tuberosum) - Zakaria, M; Hossain, MM; Mian, MA Khaleque; Hossain, T (Bangladesh Journal of Agricultural Research, 2014)
Five protocols of micro tuberization were used to induce large size microtuber in three recommended potato varieties, namely Cardinal, Diamant, and Heera under complete dark condition. Tuberization was the earliest (11.8 days) in the protocol P2 (MS + 5 mg/l BAP + 500 mg/l CCC + 8% sucrose), which was closely followed by that in P1 (12.7 days) (MS + 5 mg/l BAP + 50 mg/l coumarin + 8% sucrose). Maximum number of microtubers/flask (12.8) was obtained from the protocol P1 followed by that of P2 (11.6) that contained growth retardant; but higher average weight of microtuber was obtained in the protocols P5 (30 days old plantlet + MS media containing 40 meq K + 10 mg/l BA + 9% sucrose), P4 (MS + 10 mg/l BA + 8% sucrose), and P3 (MS + 5.0 mg/l BAP + 6% sucrose) which contained BA in absence of growth retardant. The average weight of microtuber was the highest (329.0 mg) in protocol P5, followed by that in P4 (280.7 mg), while it was the lowest in protocol P1. The variety Diamant produced maximum average weight of microtuber (246.3 mg), while Heera produced minimum (226.1 mg), which was statistically similar to Cardinal (228.7 mg). The highest percentage (52.2) of >300 mg size and lowest percentage (19.3) of <150 mg size microtuber was produced in P5 protocol in the variety Diamant. On overall consideration, all the varieties performed best with the protocol P5. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20143 Bangladesh J. Agril. Res. 39(1): 59-66, March 2014